Biomass local production systems and their managing – alternative to rural development in Slovakia - Kološta, Stanislav; Flaška, Filip (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Local production systems (LPS) focused on biomass usage represent a viable alternative to rural development, which can contribute to solve its socio-economic problems in Slovakia. The main objective of this paper was to propose a general framework for the functioning of biomass LPS in rural areas and to summarize the main points for smooth running of biomass LPS projects aimed at the resource base, method of obtaining energy from biomass, energy production cycle and a dialogue with inhabitants of municipalities where biomass LPS are to be located. Lack of experience in implementing such projects was the root cause of problems in Banská Bystrica region. Therefore, access to information, experiences form other countries and the development of appropriate formal and informal linkages are necessary for knowledge transfer and play an important role in managing biomass LPS.